The Effectiveness Using New Design Wheelchair-Bed for Dialysis Patients in Pahang Malaysia - Johan, Muhammad Aiman Bin Abu; Nizam, Mohd Nazruddin Bin Mohd; Ibrahim, Jamadeel Izwan Bin (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives:This study evaluates the effectiveness of a prototype wheelchair-bed developed for dialysis patients in Pahang, Malaysia. Background Problems: Dialysis patients often experience discomfort during long treatment sessions at dialysis centers, indicating a need for improved supportive equipment that enhances comfort and functionality. Novelty: The novelty lies in the prototype itself—a wheelchair-bed that uniquely combines mobility with reclining and bed functions, specifically designed to address the needs of dialysis patients. Research Methods: The study involved a real prototype demonstration at a dialysis center. A structured survey was administered to a simulated sample of 213 respondents, including doctors, nurses, dialysis patients, and other healthcare personnel. Finding/Results: The prototype received high overall satisfaction, with average ratings between 4.1 and 4.8 on a 5-point scale in criteria such as comfort, adjustability, ease of operation, and perceived benefits.Open-ended feedback highlighted strengths in comfort, adjustability, and caregiver convenience.Suggested improvements included reducing the device’s weight and enhancing its ventilation system. Conclusion: The findings confirm the prototype’s initial effectiveness and provide valuable, actionable insights for the design team to further refine and enhance the wheelchair-bed before broader implementation.